SOIL PROPERTIES EVALUATION OF SPATIAL VARIABILITY UNDER PIVOTS IN THE REGION OF EL-MANSOURA, GHARDAÏA DISTRICT, ALGERIA - Benbrahim Fouzi , Boutmedjet Ahmed , Benslama Abderraouf , Chikhi Faredj , Ait Aoudia Ahmed , Ghrib Toufik (Chelonian Research Foundation, 2024)
The productivity of Saharan soils under pivot is largely governed by the heterogeneity of soil properties at the field scale. The present study focused on the assessments of the spatial variability of pH, soil salinity and organic matter using a geostatistical approach, in the study area. Therefore, two pivots were selected, in the Mansoura region in Ghardaïa – district, Algeria. A set of soil samples were taken (20 samples per pivot) at top soil with depth ranging from 0 & 25cm). After soil preparation a series of analyses were carried out on pH, electrical conductivity and organic matter following Walkey-Black method. The results obtained reveal that the soils present an alkaline pH (pH=8.4± 0.1; 8.3± 0.2), the soil are not salty EC (dS/m) =1.52± 0.6; 2.1± 0.7) and have a low or moderate percentage of organic matter (OM% = 0.33± 0.22, 0.23±0.1) in Pivot 1 and Pivot 2 respectively. These results were interpolated by IDW interpolation and the effectiveness of this geostatistical model was evaluated by calculating the mean error (ME) with value (ME= 0.03, -0.02; -0.02, 0.02; 0.03, -0.003) and root mean square error (RMSE) With value (RMSE= 0.11, 0.16; 0.59, 0.72; 0.25, 0.12) in pH, electrical conductivity and Organic Matter in Pivot 1, Pivot 2 respectively. The thematic maps show a strong spatial variability at the scale of the two study areas. This research could be applied to other studies on the factors controlling the dynamics of soil properties in agricultural land, especially in a Saharan environment. It is strongly recommended that this type of study be conducted in Saharan agricultural lands and that it be extended to large-scale regions.